Introducing Neurolinguistic Programming (NLP): A Practical Guide. - Neil Shah (Icon Books, 2011)
"Neurolingustic Programming: A Practical Guide" by Neil Shah takes proven psychological techniques and helps you to use them in the real world. It's packed with exercises and activities so you can get started straight away. You can influence others and understand how they're influencing you. You can make new friends and feel more confident, achieve your goals with the power of visualization, and overcome unhappiness and think positively.